2023
DOI: 10.3390/ma16031278
|View full text |Cite
|
Sign up to set email alerts
|

Hardness Distribution of Al2050 Parts Fabricated Using Additive Friction Stir Deposition

Abstract: The solid-state additive friction stir deposition (AFSD) process is a layer-by-layer metal 3D-printing technology. In this study, AFSD is used to fabricate Al–Cu–Li 2050 alloy parts. The hardness values for various regions of the as-deposited built parts are measured, and the results are contrasted with those of the feedstock material. The as-fabricated Al2050 parts are found to have a unique hardness distribution due to the location-specific variations in the processing temperature profile. The XRD results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This configuration results in a greater susceptibility to crack growth and accelerated fracture due to the presence of layer boundary defects or weakened interfacial layers [77]. For AFSD, the layer boundaries are formed differently from a regular layer-by-layer printing because of re-stringing of the previous layer [29,31]. Saber et al investigated the layer-by-layer architecture of distinct segments within as-built AA6061 parts created via the AFSD process, employing neutron imaging techniques as a non-destructive evaluation methodology [30].…”
Section: The Effect Of Test Specimen Directionmentioning
confidence: 99%
See 2 more Smart Citations
“…This configuration results in a greater susceptibility to crack growth and accelerated fracture due to the presence of layer boundary defects or weakened interfacial layers [77]. For AFSD, the layer boundaries are formed differently from a regular layer-by-layer printing because of re-stringing of the previous layer [29,31]. Saber et al investigated the layer-by-layer architecture of distinct segments within as-built AA6061 parts created via the AFSD process, employing neutron imaging techniques as a non-destructive evaluation methodology [30].…”
Section: The Effect Of Test Specimen Directionmentioning
confidence: 99%
“…In the AFSD manufacturing process, the mixture of a high temperature and strain rate leads to dynamic recrystallization of the material being deposited [1,29,66]. Consequently, the as-deposited material exhibits smaller equiaxed grain sizes compared to the feedstock material [29,31]. Zeng et al reported a grain size of 8.5 ± 3 µm for the as-deposited AA6061 parts and 163.5 ± 96 µm for the feedstock material [29].…”
Section: Effect Of Temperature History On Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Ghadimi et al. confirmed that the top layer of the deposited Al2050 part exhibited higher microhardness (about 118 HV) than the middle layer (about 80 HV), attributing to the re‐stirring and re‐heating of the AFSD process [8] . Therefore, it is essential to understand the effect of the thermal evolution and deformation conditions on the performance and to predict the mechanical properties with in‐process feedback control of the process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, additive manufacturing and dissimilar metal welding have attracted much attention for its various advantages, such as high efficiency and easy repeatability. Nonetheless, due to the manufacturing characteristics [5][6][7], mechanical anisotropy and performance distribution may become inhomogeneous and further deep microstructural characterizations should be performed.…”
mentioning
confidence: 99%